Silicon PV module fitting equations based on experimental measurements - Sabry A.H.; Hasan W.Z.W.; Sabri Y.H.; Ab-Kadir M.Z.A. (John Wiley and Sons Ltd, 2023)
Mathematical models; Mean square error; Nonlinear equations; Photovoltaic cells; Silicon; Solar power generation; Characteristic curve; Evaluation parameters; I - V curve; Mathematical formulas; Measurement based model; Nonlinear activation functions; Root mean squared errors; Solar photovoltaics; Curve fitting